PENERAPAN NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 001 TELUK PINANG KECAMATAN GAUNG ANAK SERKA - Sri Wahyuni Sri Wahyuni; Jesi Alexander Alim Alexander Alim; Otang Kurniaman Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research has purpose to improve the ability of student in studyin mathematics by applying cooperative learning method calledNumbered Heads Together (NHT)in fourth grade SD Negeri 001 Teluk Pinang. NHT is a cooperative learningmethod, in which students are placed into groups of 4-5 people and each group are numbered 1-5. The research was conducted in April to May 2014. The subject of this research where the IV year students of SD Negeri 001 Teluk Pinang in academic year 2013/2014.The number of students was 33, they are 14 boy and 19 girls. Class data of this study is data about the outcomes of learning and cooperative learning NHT. The technique of collecting data through observation and tests, while the technique of data analysis using descriptive analysis. Data analysis can be seen from the activity of the teacher during the learning process with the implementation of cooperative learning model NHT in the first cycle by an average of 66.7%, the second cycle increased to 79% and in the third cycle an average percentage of 93.8%. In the classical completeness on the basis of scores by an average of 39.3% of learning outcomes. In the first cycle completeness percentage of 51.5%, in the second cycle completeness percentage of 63.6%, while the third cycle completeness percentage increase of 84.8%.There fore, it concludes tht applying NHT cooperative method can improve the ability of the class IV SD Negeri 001 Teluk Pinang in learning mathematics.Keywords : Method Numbered Heads Together (HNT), Mathematics.